Distinct acidic clusters and hydrophobic residues in the alternative splice domains X1 and X2 of alpha7 integrins define specificity for laminin isoforms. - Mark, Helga; Pöschl, Ernst; Lanig, Harald; Sasaki, Takako; Deutzmann, Rainer; Mark, Klaus (Journal of Molecular Biology, 2007)
The binding specificity of alpha7beta1 integrins for different laminin isoforms is defined by the X1 and X2 splice domains located in the beta-propeller domain of the alpha7 subunit. In order to gain insight into the mechanism of specific laminin-integrin interactions, we defined laminin-binding epitopes of the alpha7X1 and -X2 domains by single amino acid substitutions and domain swapping between X1 and X2. The interaction of mutated, recombinantly prepared alpha7X1beta1 and alpha7X2beta1 heterodimers with various laminin isoforms was studied by surface plasmon resonance and solid phase binding assays. The data show that distinct clusters of surface-exposed acidic residues located in different positions of the X1 and the X2 loops are responsible for the specific recognition of laminins. These residues are conserved between the respective X1 or X2 splice domains of the alpha7 chains of different species, some also in the corresponding X1/X2 splice domains of alpha6 integrin. Interestingly, ligand binding was also modulated by mutating surface-exposed hydrophobic residues (alpha7X1L205, alpha7X2Y208) at positions corresponding to the fibronectin binding synergy site in alpha5beta1 integrin. Mutations in X1 that affected binding to laminin-1 also affected binding to laminin-8 and -10, but not to the same extent, thus allowing conclusions on the specific role of individual surface epitopes in the selective recognition of laminin-1 versus laminins -8 and -10. The role of the identified epitopes was confirmed by molecular dynamics simulations of wild-type integrins and several inactivating mutations. The analysis of laminin isoform interactions with various X1/X2 chimaera lend further support to the key role of negative surface charges and pointed to an essential contribution of the N-terminal TARVEL sequence of the X1 domain for recognition of laminin-8 and -10. In conclusion, specific surface epitopes containing charged and hydrophobic residues are essential for ligand binding and define specific interactions with laminin isoforms.

Functional consequence of fibulin-4 missense mutations associated with vascular and skeletal abnormalities and cutis laxa - Sasaki, Takako; Hanisch, Franz-Georg; Deutzmann, Rainer; Sakai, Lynn Y.; Sakuma, Tetsushi; Miyamoto, Tatsuo; Yamamoto, Takashi; Hannappel, Ewald; Chu, Mon-Li; Lanig, Harald; Mark, Klaus (Matrix Biology, 2016)
Fibulin-4 is a 60kDa calcium binding glycoprotein that has an important role in development and integrity of extracellular matrices. It interacts with elastin, fibrillin-1 and collagen IV as well as with lysyl oxidases and is involved in elastogenesis and cross-link formation. To date, several mutations in the fibulin-4 gene (FBLN4/EFEMP2) are known in patients whose major symptoms are vascular deformities, aneurysm, cutis laxa, joint laxity, or arachnodactyly. The pathogenetic mechanisms how these mutations translate into the clinical phenotype are, however, poorly understood. In order to elucidate these mechanisms, we expressed fibulin-4 mutants recombinantly in HEK293 cells, purified the proteins in native forms and analyzed alterations in protein synthesis, secretion, matrix assembly, and interaction with other proteins in relation to wild type fibulin-4. Our studies show that different mutations affect these properties in multiple ways, resulting in fibulin-4 deficiency and/or impaired ability to form elastic fibers. The substitutions E126K and C267Y impaired secretion of the protein, but not mRNA synthesis. Furthermore, the E126K mutant showed less resistance to proteases, reduced binding to collagen IV and fibrillin-1, as well as to LTBP1s and LTBP4s. The A397T mutation introduced an extra O-glycosylation site and deleted binding to LTBP1s. We show that fibulin-4 binds stronger than fibulin-3 and -5 to LTBP1s, 3, and 4s, and to the lysyl oxidases LOX and LOXL1; the binding of fibulin-4 to the LOX propeptide was strongly reduced by the mutation E57K. These findings show that different mutations in the fibulin-4 gene result in different molecular defects affecting secretion rates, protein stability, LOX-induced cross-linking, or binding to other ECM components and molecules of the TGF-? pathway, and thus illustrate the complex role of fibulin-4 in connective tissue assembly.
EVALuna2:10217

Loss of fibulin-4 results in abnormal collagen fibril assembly in bone, caused by impaired lysyl oxidase processing and collagen cross-linking - Sasaki, Takako; Stoop, Reinout; Sakai, Takao; Heß, Andreas; Deutzmann, Rainer; Schlötzer-Schrehardt, Ursula; Chu, Mon-Li; Von Der Mark, Klaus (Matrix Biology, 2016)
The extracellular matrix protein fibulin-4 has been shown to be indispensable for elastic fiber assembly, but there is also evidence from human mutations that it is involved in controlling skeletal development and bone stability. Fibulin-4 mutations were identified in patients suffering from vascular abnormality and/or cutis laxa, and some of these patients exhibited bone fragility, arachnodactyly and joint laxity. In order to elucidate the role of fibulin-4 in bone structure and skeletal development, we analyzed structural changes in skeletal tissues of Fbln4(-/-) mice. Immunostaining confirmed that fibulin-4 is highly expressed in cartilage, bone, ligaments and tendons. No morphological abnormalities were found in the skeleton of Fbln4(-/-) mice as compared to wild type littermates except forelimb contractures as well as unusually thick collagen fibrils. Furthermore, fibulin-4 deficiency caused enhanced susceptibility of bone collagen for acid extraction, consistent with significantly reduced lysylpyridinoline and hydroxylysylpyridinoline cross-links in bone. In accordance with that, the amount of lysyl oxidase in long bones and calvaria was strongly decreased and proteolytic activation of lysyl oxidase was reduced in fibulin-4 deficient osteoblasts, while addition of recombinant fibulin-4 rescued the activation. The finding suggested that fibulin-4 is important for the proteolytic activation of lysyl oxidase which has a pivotal role in cross-linking of collagen and elastin.
EVALuna2:10209

LOXL1 deficiency in the lamina cribrosa as candidate susceptibility factor for a pseudoexfoliation-specific risk of glaucoma - Schlötzer-Schrehardt, Ursula; Hammer, Christian; Krysta, Anita W.; Hofmann-Rummelt, Carmen; Pasutto, Francesca; Sasaki, Takako; Kruse, Friedrich; Zenkel, Matthias (Ophthalmology, 2012)
To test the hypothesis that a primary disturbance in lysyl oxidase-like 1 (LOXL1) and elastin metabolism in the lamina cribrosa of eyes with pseudoexfoliation syndrome constitutes an independent risk factor for glaucoma development and progression.Observational, consecutive case series.Posterior segment tissues obtained from 37 donors with early and late stages of pseudoexfoliation syndrome without glaucoma, 37 normal age-matched control subjects, 5 eyes with pseudoexfoliation-associated open-angle glaucoma, and 5 eyes with primary open-angle glaucoma (POAG).Protein and mRNA expression of major elastic fiber components (elastin, fibrillin-1, fibulin-4), collagens (types I, III, and IV), and lysyl oxidase crosslinking enzymes (LOX, LOXL1, LOXL2) were assessed in situ by quantitative real-time polymerase chain reaction, (immuno)histochemistry, and light and electron microscopy. Lysyl oxidase-dependent elastin fiber assembly was assessed by primary optic nerve head astrocytes in vitro.Expression levels of elastic proteins, collagens, and lysyl oxidases in the lamina cribrosa.Lysyl oxidase-like 1 proved to be the major lysyl oxidase isoform in the normal lamina cribrosa in association with a complex elastic fiber network. Compared with normal and POAG specimens, lamina cribrosa tissues obtained from early and late stages of pseudoexfoliation syndrome without and with glaucoma consistently revealed a significant coordinated downregulation of LOXL1 and elastic fiber constituents on mRNA and protein level. In contrast, expression levels of collagens and other lysyl oxidase isoforms were not affected. Dysregulated expression of LOXL1 and elastic proteins was associated with pronounced (ultra)structural alterations of the elastic fiber network in the laminar beams of pseudoexfoliation syndrome eyes. Inhibition of LOXL1 interfered with elastic fiber assembly by optic nerve head astrocytes in vitro.The findings provide evidence for a pseudoexfoliation-specific elastinopathy of the lamina cribrosa resulting from a primary disturbance in LOXL1 regulation and elastic fiber homeostasis, possibly rendering pseudoexfoliation syndrome eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression.
EVALuna2:1645

Molecular dynamics simulations on human fibulin-4 mutants D203A and E126K reveal conformational changes in EGF domains potentially responsible for enhanced protease lability and impaired extracellular matrix assembly - Sasaki, Takako; von der Mark, Klaus; Lanig, Harald (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2019)
Fibulin-4 is a 50 kDa glycoprotein of elastic fibers and plays an important role in development and function of elastic tissues. Fibulin-4 consists of a tandem array of five calcium-binding epidermal growth factor-like modules flanked by N- and C-terminal domains. Mutations in the human fibulin-4 gene EFEMP2 have been identified in patients affected with various arteriopathies including aneurysm, arterial tortuosity, or stenosis, but the molecular basis of most genotype-phenotype correlations is unknown. Here we present biochemical and computer modelling approaches designed to gain further insight into changes in structure and function of two fibulin-4 mutations (E126K and D203A), which are potentially involved in Ca2+ binding in the EGF2 and EGF4 domain, respectively. Using recombinantly produced fibulin-4 mutant and wild type proteins we show that both mutations introduced additional protease cleavage sites, impaired extracellular assembly into fibers, and affected binding to to fibrillin-1, latent TGF-β-binding proteins, and the lysyl oxidase LOXL2. Molecular dynamics studies indicated that the E126K and D203A mutations do not necessarily result in a direct loss of the complexed Ca2+ ion after 500 ns simulation time, but in significantly enhanced fluctuations within the connecting loop between EGF3 and EGF4 domains and other conformational changes. In contrast, intentionally removing Ca2+ from EGF4 (D203A ΔCa) predicted dramatic changes in the protein structure. These results may explain the changes in protease cleavage sites, reduced secretion and impaired extracellular assembly of the E126K and D203A fibulin-4 mutants and provide further insight into understanding the molecular basis of the associated clinical phenotype
Keywords: Extracellular matrix protein; Mutation; Matrix assembly; Computer simulation; Fibulin-4